RESPIRATION RATES AND HEART RATE VARIABILITY IN HEALTHY VOLUNTEERS IN BIOFEEDBACK CONNECTION - Kulik, A.L.; Zaderihin, A.K.; Shulgin, V.I.; IabluchanskyiМ.I. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
At the 4 healthy volunteers aged 22 to 29 years (2 men and 2 women) with a body mass index from 21 to 23 individual characteristics and general regularities of heart rate variability (HRV) frequency dependence were examined. It is shown that the frequency of paced breathing significantly affects the power and structure of the HRV spectrum and regulation in general. Increasing of LF domain of the HRV occurs on breathing frequencies 5-8 per minute. Increasing of HF domain of HRV occurs on breathing frequencies 9-13 per minute. Changes in TP of HRV are more related to the LF and less to HF domain. Biofeedback with different programs of changing in the paced breath frequency can be a powerful tool of intervention in the regulation and quality of life.